On the occasion of my last afternoon - Gibbons, Kaye (New York : G. P. Putnam's Sons, 1998)
A Southern woman describes her life--from childhood on a plantation with a tyrannical father, to Civil War nurse in a military hospital with her surgeon husband, to pro-abolitionist in old age.
Keywords: Women -- Southern States -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; Fiction